2023
DOI: 10.1002/app.53784
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoropolyether methyl propionate polysiloxane coating with high hydrophobicity and low dielectric property

Abstract: Developing materials with a combination of superior properties such as hydrophobicity and low dielectric is very challenging. This work proposes a design strategy based on the synergistic effect of silicon fluorine to fabricate fluorous silicon materials with excellent hydrophobicity and dielectric properties. Perfluoropolyethyl propionate polysiloxane (PEPS) with different grafting ratios was synthesized by the reaction of polymethylhydrosiloxane (PMHS) and perfluoropolyethyl methacrylate (PPM) hydrosilane. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…59 Generally, a high number and better morphology of pseudopods is an indicator of the higher viability of a cell. 6 According to the statistical results, the number of pseudopods of cells cultured with rMBG/Sr was much bigger than those of the control group and the cells with rMBG, and the NSI of cells with the rMBG/Sr was lower. These results indicated that cells with the rMBG/Sr group had better morphology and higher viability.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…59 Generally, a high number and better morphology of pseudopods is an indicator of the higher viability of a cell. 6 According to the statistical results, the number of pseudopods of cells cultured with rMBG/Sr was much bigger than those of the control group and the cells with rMBG, and the NSI of cells with the rMBG/Sr was lower. These results indicated that cells with the rMBG/Sr group had better morphology and higher viability.…”
Section: Resultsmentioning
confidence: 94%
“…To this end, excellent biocompatibility, suitable microstructure and effective cell inductivity of the materials are the key requirements. 6–8 Furthermore, to facilitate wound healing, the materials should be able to induce rapid angiogenesis, as sufficient blood vessels are needed to effectively transport nutrients and oxygen, recruit tissue cells, and metabolize tissue waste. 9–11…”
Section: Introductionmentioning
confidence: 99%